Modern view on the issues of diagnosis and verification of axillary lymph nodes involvement in early breast cancer - Irina V. Kolyadina (IP Habib O.N., 2020)
The involvement of axillary lymph nodes is one of the most important prognostic factors, significantly affecting the treatment strategy for early breast cancer (BC). The risk of axillary lymph node metastases depends directly on a number of factors (age of women, size of tumor, presence of lymphovascular invasion and biological characteristics of cancer). The evaluation of regional lymph node status in patients with early BC includes the clinical examination of regional zones and the ultrasound study (US), using these methods can help to study lymph nodes shape, borders, margins and structure. The sensitivity of ultrasound in the evaluation of regional lymph nodes status directly depends on the biological subtype of the tumor; the minimum level of ultrasound sensitivity in the evaluation of lymph nodes status is detected for luminal HER2-negative cancer (less than 40%), and maximum sensitivity is detected for triple negative and HER2-positive subtypes (6871%). Clinical examination and modern ultrasound are the most accessible methods for the evaluation of regional lymph nodes status, but the possibility to misjudge metastatic process can be detected in 1/4 of patients. Verification of the diagnosis in the preoperative phase (fine-needle aspiration biopsy/core-needle biopsy under ultrasound guidance) allows minimize the number of errors for the regional staging. The sentinel lymph node biopsy (SLNB) is the gold standard of regional treatment in patients with early stage BC, nowadays. The randomized trials (NSABP B-32, ACOSOG q0011) show the safety of recession of performing regional lymph node dissection in favor of SLNB not only in case of clinically negative lymph nodes, but also in patients with metastases in 2 sentinel lymph nodes, upon condition that organ-conservative treatment and subsequent radiation therapy will be used. High-quality regional staging, the choice of the therapeutic algorithm in accordance with the biological characteristics of carcinoma, the application of the most effective modern drug regimes, the optimal radiation therapy allow not only minimize the extent of surgery, but also achieve high long-term survival results, provide excellent functional results and high quality of life in patients with the involvement of axillary lymph nodes.